Predictive risk stratification using HEART (history, electrocardiogram, age, risk factors, and initial troponin) and TIMI (thrombolysis in myocardial infarction) scores in non-high risk chest pain patients: An African American urban community based hospital study. Issue 32 (August 2019) - Bhattacharya, Priyanka T.; Golamari, Reshma R.; Vunnam, Sandhya; Moparthi, Smitha; Venkatappa, Neethi; Dollard, Denis J.; Missri, Jose; Yang, Wei; Kimmel, Stephen E.
Abstract : Abstract: Validated risk scoring systems in African American (AA) population are under studied. We utilized history, electrocardiogram, age, risk factors, and initial troponin (HEART) and thrombolysis in myocardial infarction (TIMI) scores to predict major adverse cardiovascular events (MACE) in non-high cardiovascular (CV) risk predominantly AA patient population. A retrospective emergency department (ED) charts review of 1266 chest pain patients where HEART and TIMI scores were calculated for each patient. Logistic regression model was computed to predict 6-week and 1-year MACE and 90-day cardiac readmission. Decision curve analysis (DCA) was constructed to differentiate between clinical strategies in non-high CV risk patients. Of the 817 patients included, 500 patients had low HEART score vs. 317 patients who had moderate HEART score. Six hundred sixty-three patients had low TIMI score vs. 154 patients had high TIMI score. The univariate logistic regression model shows odds ratio of predicting 6-week MACE using HEART score was 3.11 (95% confidence interval [CI] 1.43–6.76, P  = .004) with increase in risk category from low to moderate vs. 2.07 (95% CI 1.18–3.63, P  = .011) using TIMI score with increase in risk category from low to high and c-statistic of 0.86 vs. 0.79, respectively. DCA showed net benefit of using HEART score is equally predictive of 6-week MACE when compared to TIMI. In non-high CV risk AA patients, HEART score is better predictive tool for 6-week MACE when compared to TIMI score. Furthermore, patients presenting to ED with chest pain, the optimal strategy for a 2% to 4% miss rate threshold probability should be to discharge these patients from the ED. Abstract : Supplemental Digital Content is available in the text